Atypical seasonal variability of the Kuroshio Current in 2018 - Wang, Fujun; Zhang, Linlin; Feng, Junqiao; Wang, Qingye; Hu, Dunxin (Frontiers in Marine Science, 2025)
IntroductionUsing three moorings deployed at 122.7°E, 123°E, and 123.3°E along 18°N from January 2018 to May 2020, this study investigates the seasonal variability of the Kuroshio Current (KC).MethodsSensitive experiments were conducted with the Regional Ocean Modeling System (ROMS).ResultsIn 2019, the KC exhibited a typical seasonal cycle, being relatively strong during spring, summer, and winter, with the weakest flow occurring in autumn. In contrast, the KC displayed an atypical seasonal cycle in 2018, characterized by two distinct intraseasonal intensification events in late September and early November. The ROMS experiments revealed that local winds within the region (120°E–125°E, 15°N–20°N) were the primary driver of this atypical cycle. During the two key periods, persistent negative wind stress curl anomalies east of the mooring stations induced integrated positive sea surface height anomalies and corresponding northward meridional velocity anomalies via geostrophic balance.DiscussionIn 2019, the wind stress curl anomaly phases reversed compared to 2018, leading to the absence of the two peaks observed in the previous year.